2018
DOI: 10.1039/c7tb02614e
|View full text |Cite
|
Sign up to set email alerts
|

TiO2-coated luminescent porous silicon micro-particles as a promising system for nanomedicine

Abstract: Porous silicon (pSi), a sponge-like material, was coated by ALD with a TiO2 layer to stabilize photoluminescence in biological media. In vitro results open the way to promising applications in nanomedicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In this regard, it has been reported that the microbial chemoattractant N-formyl-methionyl-leucyl-phenylalanine (fMLP) synergized the ability of ORMOSIL nanoparticles to stimulate the release of cytokines by human leukocytes [ 45 ]. Moreover, the simultaneous addition of LPS and porous silicon-TiO 2 microparticles was much more effective than incubation with LPS alone to induce IL-12 and TNF-α secretion by human DCs [ 46 ]. Therefore a synergy between nanoparticles and microbial molecules is not a so rare and unexpected event, although it is usually poorly studied by researchers dealing with nanostructures.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been reported that the microbial chemoattractant N-formyl-methionyl-leucyl-phenylalanine (fMLP) synergized the ability of ORMOSIL nanoparticles to stimulate the release of cytokines by human leukocytes [ 45 ]. Moreover, the simultaneous addition of LPS and porous silicon-TiO 2 microparticles was much more effective than incubation with LPS alone to induce IL-12 and TNF-α secretion by human DCs [ 46 ]. Therefore a synergy between nanoparticles and microbial molecules is not a so rare and unexpected event, although it is usually poorly studied by researchers dealing with nanostructures.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a nanoparticle unable to activate immune cells and, therefore, generally considered biocompatible, could instead enhance the pro-inflammatory effect of some microorganisms or their derivatives [ 18 , 43 , 44 , 45 ] through a cooperative event named “cell priming” [ 46 , 47 ]. This implies that, if this apparently harmless nanoparticle is administered to the patient in the presence of other agents such as pathogenic fungi, bacteria, or viruses, it might cause unwanted dangerous effects as it can induce a hyper-responsiveness of leukocytes to the above-mentioned agents.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we explore the use of ALD to stabilize and potentially functionalize solution-processed thin films of Si NPs (Figure ). Despite the recently highlighted potential of Si NP films for a wide range of applications, like photovoltaics, thin-film transistors, , and plasmonics, investigations of the impact of an ALD infilling on their stability and physicochemical properties are still in a very initial stage. , In a previous work, it has been found that encapsulation of FETs based on Si NP films with Al 2 O 3 deposited with ALD led to a suppression of hysteresis in the transistor characteristics . For our studies, we prepared films of randomly distributed Si NPs with ultrashort surface ligands (Si–H termination) using wet chemistry and spray-coating and then used ALD to infill the films with Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%